REPRESENTASI SULTAN DAN KEPEMIMPINAN DALAM MEDIA MASSA LOKAL DI MALUKU UTARA - Tommy Christommy; NFN Nazarudin (Masyarakat Linguistik Indonesia, 2021)
Van Klinken (2007) argued that in Indonesia’s autonomy era, sultanship has become perhaps the symbol par excellence of local identity. It is part of the communitarian turn in Indonesian politics after the end of the New Order. This becomes one of the factors that revived identities or invented it at a great rate, especially at the district level. Within those backgrounds, this research aims to investigate how the sultan and sultanship in Ternate represented by the local media. We used qualitative approach to capture the representation of sultan by analyzing the newspaper published in Malut Post, the biggest local newspaper in North Maluku. By utilizing a qualitatively processed key analysis with the NVIVO software, we analyze Saturday’s newspaper published in 2012—2017 using some keywords semantically related to sultan and kesultanan. Moreover, we also analyzed the semantics relations of the related keywords such as kolano and jou to figure out its collocation in the corpus data. Based on our findings, we figure out that sultan is represented more dominan in the media compare to kesultanan. On the one side, the local media captured the role of sultan as a figure, and also a father. However, on the other side, the media also capture the conflict that has happened inside the kesultanan, especially related with the new Sultan election process.